Non-porous thrombi are less pervious and easier to be retrieved: implication from scanning electron microscopy study. (28th March 2022) - He, Yaode; Xu, Jinjin; Zhong, Wansi; Chen, Zhicai; Zhou, Ying; Li, Jiaping; Luo, Zhongyu; Lou, Min
Abstract : Background: Scanning electron microscopy (SEM) studies found that the porosity of thrombi might vary among individuals. However, its relationship with the clinical presentation and efficacy of mechanical thrombectomy (MT) remains unknown. We aimed to characterize the ultrastructure of thrombi and explore its association with the complexity of MT and clot perviousness. Methods: SEM was used to observe the morphological features of different components of thrombi obtained from patients with anterior circulation large vessel occlusion undergoing MT and to determine the porosity of thrombi by semi-quantitative analysis. Non-porous thrombi were defined as thrombi with porosity <2%. Clot perviousness was also evaluated using thrombus attenuation increase on CT perfusion (TAIctp ). We assessed the complexity of MT by attempts of retrieval >3 and procedural duration >60 min, defined as the time interval between groin puncture and recanalization. Results: A total of 49 thrombi were analyzed and 31 (63.3%) were classified as non-porous thrombi. The presence of non-porous thrombi was negatively associated with procedure >60 min (OR 0.152, 95% CI 0.031 to 0.734, p=0.019) and attempts >3 (OR 0.194, 95% CI 0.046 to 0.822, p=0.026) after adjustment. Additionally, receiver operating characteristic curve analysis indicated that TAIctp <17.9 Hounsfield units could predict the presence of non-porous thrombi with an area under the curve of 0.915. Conclusions: Non-porous thrombi on SEM are easier to be retrieved during MT and could be identified as less pervious clots on CT images.